2013
DOI: 10.1371/journal.pone.0060570
|View full text |Cite
|
Sign up to set email alerts
|

The FTO A/T Polymorphism and Elite Athletic Performance: A Study Involving Three Groups of European Athletes

Abstract: ObjectiveThe FTO A/T polymorphism (rs9939609) is a strong candidate to influence obesity-related traits. Elite athletes from many different sporting disciplines are characterized by low body fat. Therefore, the aim of this study was to assess whether athletic status is associated with the FTO A/T polymorphism.Subjects and MethodsA large cohort of European Caucasians from Poland, Russia and Spain were tested to examine the association between FTO A/T polymorphism (rs9939609) and athletic status. A total of 551 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Similar results were found in a study reported by Eynon et al. 25 In this study, a total of 551 Caucasian subjects of European descent (Poland, Russia and Spain) were evaluated. At the end of the study, no association between FTO gene polymorphism and the physical performance of athletes was found.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were found in a study reported by Eynon et al. 25 In this study, a total of 551 Caucasian subjects of European descent (Poland, Russia and Spain) were evaluated. At the end of the study, no association between FTO gene polymorphism and the physical performance of athletes was found.…”
Section: Discussionsupporting
confidence: 90%
“…Although these findings in West European populations support the hypothesis that the iron-increasing HFE rs1799945 G allele is favorable for endurance performance, replication studies in different ethnic groups using different designs are warranted. This approach leads to the exclusion of false-positive genetic associations (Eynon et al 2013;Zarebska et al 2017;Papadimitriou et al 2018;Yvert et al 2018;Guilherme et al 2019;Pickering et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid false-positive results, casecontrol studies should have at least one replication with additional athletic and nonathletic cohorts from different populations [2]. Since endurance and power are located at opposite extremes of the muscle performance continuum, the comparison of allelic frequencies between endurance and power athletes is also the way to identify endurance/power markers [3].…”
Section: Introductionmentioning
confidence: 99%